Aerosol processes in polar regions : from formation to climatic implications - Kyrö, Ella-Maria (Helsingin yliopisto, 2014)
Atmospheric aerosols affect our health, air quality, visibility and climate. They can impact the climate trough their ability to interact with radiation and to alter cloud properties by acting as cloud condensation nuclei (CCN) or ice nuclei (IN). Globally, aerosols cool the climate, but locally their effect may be opposite. Their climatic effects are determined by their concentration, size distribution and chemical composition as well as their vertical and spatial distribution and the underlying surface type. Currently, the largest uncertainties in estimating our future climate are related to atmospheric aerosols and their intearctions with climate. Polar regions are experiencing faster warming than the Earth on average. This enhanced warming leads to many dramatic changes in the cryosphere, including rapid shrinkage of Arctic summer sea ice. Arctic ampli cation also decreases the temperature gradient between the Arctic and polar air masses. Both of these changes feed back to the atmospheric dynamics and thus the transport of pollutants into the Arctic. The rapid climate change alters also the sources - both natural and anthropogenic - and sinks of secondary aerosols in polar regions. Therefore, it is crucial to understand the formation and growth mechanisms of atmospheric aerosols in these areas in order to assess their climatic effects. High latitudes also offer a great natural laboratory to study the aerosol dynamics and timescales for reaching climatically relevant sizes or obtaining a balance between sources and sinks, with very little anthropogenic influence. Moreover, as the precipitation amount and patterns will change in the future, the removal of aerosols is also subject to change. Quantifying this requires parameterization for climate models. This thesis adds to the understanding of all of these aforementioned parts in the aerosol processes and their climatic effects in polar regions. It offers the fi rst observations of Antarctic new particle formation (NPF) from continental biogenic precursors and ...